2021
DOI: 10.1038/s41598-021-03557-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and metabolic analyses revealed the modulatory effect of vernalization on glucosinolate metabolism in radish (Raphanus sativus L.)

Abstract: Vernalization is the process by which long-term cold like winter triggers transition to flowering in plants. Many biennial and perennial plants including Brassicaceae family plants require vernalization for floral transition. Not only floral transition, but dynamic physiological and metabolic changes might also take place during vernalization. However, vernalization-mediated metabolic change is merely investigated so far. One of secondary metabolites found in Brassiceceae family plants is glucosinolates (GSLs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Similarly, CYP79F1 , another gene involved in glucosinolate metabolism, was also downregulated in 21-week cold-treated main stem ( Falasca et al., 2010 ). Moreover, the inhibitory role of long-term cold exposure on indole glucosinolates content was revealed in vernalized radish plants ( Nugroho et al., 2021 ). Our study suggests that the inhibition by long-term cold of specific glucosinolate-derived compounds in the rooting environment may influence hormone signaling pathways, especially auxin, potentially affecting the growth of adventitious roots ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CYP79F1 , another gene involved in glucosinolate metabolism, was also downregulated in 21-week cold-treated main stem ( Falasca et al., 2010 ). Moreover, the inhibitory role of long-term cold exposure on indole glucosinolates content was revealed in vernalized radish plants ( Nugroho et al., 2021 ). Our study suggests that the inhibition by long-term cold of specific glucosinolate-derived compounds in the rooting environment may influence hormone signaling pathways, especially auxin, potentially affecting the growth of adventitious roots ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vernalization accelerates plant development from the vegetative to the reproductive stage, leading to considerable changes in the metabolite profiles of plants [ 31 ]. This study also confirmed that the vernalization-like low-temperature treatment process in mushrooms has similar metabolic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Glucosinolates were analyzed from 2-week-old R-o-18 and brclf mutant in accordance with a previously described protocol ( Nugroho et al., 2021 ). They were extracted from whole fresh tissue samples with 70% aqueous methanol (methanol:water 70:30, v:v) at 70°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%